PENERAPAN SUPERVISI KUNJUNGAN KELAS UNTUK MENINGKATKAN KINERJA GURU SD NEGERI 2 KALIMANGGIS KECAMATAN KALORAN, TEMANGGUNG - Danurwati, Suprih; Slameto, Slameto (Universitas Kristen Satya Wacana, 2015)
Suprih Danurwati, 942013161. Implementation of supervision class visiting to increase teacherâs performance of SD Negeri 2 Kalimanggis District of Kaloran.Â Thesis. The graduatiton Program Master of Management Education Satya WacanaÂ Christian University Salatiga. Supervisor Prof. Dr. Slameto, M.Pd. This study is to determine that through the implementation of supervision class visiting can improve the performance of teachers in the learning management. TheÂ subjects of this study are teachers in SD Negeri 2 Kalimanggis, Kaloran, Temanggung. Â The procedure used in this study consists of a series of three main activities undertakenÂ in a repeating cycle, including (a) plan, (b) action by observation, and (c) reflection.Â research approach using action research methods, while the method of data collectionÂ using the study documentation, observations, questionnaires, and interviews. TheÂ results showed an increasing in the ability of teachers to prepare lesson plans andÂ manage the learning of the first act, second, until the third act. The inference thatÂ supervision class visiting that can improve the performance of teachers in the learningÂ management. Suggestions given to teachers, is takingÂ advantage of supervisionÂ activities as a source of information to improve the competence and performance,Â for principals use the results of this study as a reference in conducting research, while for school superintendent will use the results of this study as one of the referencesÂ in activity guidance to the heads of schools and teachers to improve their performance.